El control interno en la contratación pública: estudio de caso múltiple - Naranjo Vaca, Myriam Johanna (2023)
At a global level, the report of the Committee of Sponsoring Organizations of the Treadway Commission (COSO) brought together various perspectives on internal control through the publication of a model for the management of entities, called Internal Control - Integrated Framework, with the aim of promoting efficiency and transparency in the use of resources. At the national level, in November 1977 the "General Comptroller of the State" (CGE) consigned the "Technical Standards for Internal Control" and in 2002 issued the Internal Control Standards based on the COSO model, with which the efficient and adequate administration of the resources and goods that are within the public sector can be ensured (Controller's Office, General of the State, 2014). The present investigation studies the influence of internal control through the COSO model in public procurement processes for Insignificant Amounts in public companies in the city of Riobamba through a multiple case study, where the analysis units are: Public Company - Municipal Company of Potable Water and Sewerage of Riobamba (EP EMAPAR) and the Electric Company Riobamba S.A. (EERSA). Regarding the methodology, the research presents a qualitative approach, the methods used are deductive and inductive, analytical and synthetic; while the research instruments were an internal control questionnaire and an observation sheet. The results obtained reveal non-compliance with the regulations related to public procurement, and that the components of internal control according to the COSO Model are not achieved satisfactorily.